Mobile Health applications - untapped potential - Koraćević, Maja; Jovanović, Aleksandar; Pavlović, Dragana; Catić-Đorđević, Aleksandra (Archives of Pharmacy, 2022)
Today, there are a number of applications that allow you to monitor physical activity and health parameters or schedule a medical examination, and can also help you recognize a health problem and react in time. The aim of the present study was to assess the usage of health applications (HApps, health-related mobile and/or web applications) among citizens in Serbia. The anonymous online questionnaire was distributed via social media in the spring of 2020. Data were processed using the IBM SPSS. 506 respondents participated in the research, of which 155 were from the health profession. The majority of respondents were female (73.9%), and the average age was 36.88 ± 11.22. About half of the respondents (48.2%) have a university degree, and 74.9% are employed. Installed HApps on phone/computer have 18.2% of respondents, with a statistically significant difference (p <0.01) between health professionals (25.8%) and non-health (14.8%). The most commonly used HApps among health professionals are those related to their professional work (14.7%), followed by general health (3.8%) and specific diseases (1.9%). Non-health professional respondents mostly used applications related to general health (5.4%), fitness (2.0%) and the chosen doctor (1.4%). Only 0.6% of citizens used COVID-19 pandemic applications. The importance of HApps is still not sufficiently recognized in Serbia. Given the potential in controlling chronic diseases and other health conditions, especially among a population with limited access to health care and health information, they should be more integrated into the health system.